The Mountain Adventure - "Blyton, Enid" (Macmillan Children's Books: London, 2001)
A mad genius plot, this one, with the children staying in a Welsh farmhouse and discovering peculiar happenings up at the local mountain. Strange noises rumble from it, wolves roam the slopes and crimson smoke issues from the top
Keywords: Action and adventure fiction